2015
DOI: 10.1103/physrevd.91.064055
|View full text |Cite
|
Sign up to set email alerts
|

Magnetofluid dynamics in curved spacetime

Abstract: A grand unified field M µν is constructed from Maxwell's Field tensor and appropriately modified flow field, both non-minimally coupled to gravity, to analyze the dynamics of hot charged fluids in curved background space-time. With a suitable 3 + 1 decomposition, this new formalism of the hot fluid is then applied to investigate the vortical dynamics of the system. Finally, the equilibrium state for plasma with non-linear coupling through Ricci scalar R to gravity is investigated to derive a double Beltrami eq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…For special astrophysical conditions, canonical vorticity would also have a quantum-mechanical part [see (Mahajan & Asenjo 2011;Asenjo & Mahajan 2015) for spinning plasmas], even a general relativistic component [see e.g. (Bhattacharjee et al 2015) for Black Hole accretion disks] in addition to the electromagnetic, kinetic and thermal contributions. For most applications these corrections are negligibly small.…”
Section: Model Equationsmentioning
confidence: 99%
“…For special astrophysical conditions, canonical vorticity would also have a quantum-mechanical part [see (Mahajan & Asenjo 2011;Asenjo & Mahajan 2015) for spinning plasmas], even a general relativistic component [see e.g. (Bhattacharjee et al 2015) for Black Hole accretion disks] in addition to the electromagnetic, kinetic and thermal contributions. For most applications these corrections are negligibly small.…”
Section: Model Equationsmentioning
confidence: 99%
“…This requires extending the definition of classical generalized vorticity to relativistic plasmas. The relativistic formalism, termed 'magnetofluid unification' (henceforth the magnetofluid formalism) and first proposed in ( [12]) and later extended in [13,14], replaces the regular fluid vorticity ( ∇ × V ) with a composite thermo-kinetic fluid vorticity ( ∇×GΓ V ) where G is the thermodynamic factor and Γ is the Lorentz factor.…”
Section: Introductionmentioning
confidence: 99%
“…The earlier special relativistic theory [9] was extended to explore general relativistic effects in Refs. [1][2][3][4][5]. It was shown that a combination of gravity modified Lorentz factor of the fluid element and the spatial variation of plasma thermodynamics, leads to an additional (to the special relativistic mechanism [11,12]) source that creates a vorticity seed out of a state with no initial vortic- * Electronic address: felipe.asenjo@uai.cl † Electronic address: mahajan@mail.utexas.edu ity.…”
Section: Introductionmentioning
confidence: 99%